A reminiscent review on leprosy. Issue 1 (January 2015) - Krishnan, Sugashini Padmavathy; Kamalanathan, Arunagiri; John, James; Gopalakrishnan, Sangeetha
<x xml:space="preserve">Abstract</x> Leprosy is caused by Mycobacterium leprae and has been known since biblical times. It was first discovered by the Norwegian physician Gerhard Armauer Hansen in 1873. Despite being the first pathogen to be described, it is yet to be clearly understood owing to the uncultivable nature. Leprosy has been a major public health problem in tropical countries for many decades. Leprosy still persists as a significant burden on public health worldwide. This disease is transmitted by close and prolonged contact through inhalation of the bacilli contained in nasal secretion or through skin erosions. Early diagnosis of subclinical or earner-state leprosy has been problematic. There is a substantial decrease in the prevalence of leprosy, but it still persists in a few regions of the world, India being one of them. However, repost incidence from this region has not been reported in last few years. This review article aims to discuss the aetiology, epidemiology and clinical aspects of leprosy with a retrospective view.